Covid-19 as paideia: reviewing the theological meaning of Covid-19 based on concept of the paideia in Hebrews 12:4-13 - Hakh, Samuel Benyamin (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
Discussions regarding the Covid-19 pandemic have been carried out by experts in the field of theology. They understood the pandemic as only punishment from God. The question that arises is, is the Covid-19 pandemic, solely a punishment from God? This question arises because, if God is only understood as an angry God, then that view will lead people to understand that God is evil. This article aims to examine the theological meaning of the Covid-19 pandemic based on the idea of paideia in Hebrews 12:4-13. My thesis is, Covid-19 is not only a form of punishment but also a manifestation of God's love as well. The research method I use is qualitative research. Through that method, I offer a new perspective on the meaning of Covid-19 and demonstrate the theological meaning of Covid-19 as a form of education from God to shape human character for a better future.